Materialismo e atitudes do consumo e compra entre os docentes da educação básica - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
This research investigated the relationship between consumption attitudes (impulsiveness, rationality, and compulsiveness) and materialism among basic education teachers, combining a Systematic Literature Review (SLR) and a quantitative empirical study. The SLR, conducted according to the PRISMA 2020 protocol, analyzed 16 articles and identified four main axes: psychological factors (such as anxiety and self-discrepancy between the "real self" and the "ideal self"), social factors (media influence and peer pressure), the relationship between materialism and well-being (with evidence of negative impacts on mental health), and the role of socioeconomic context (income, gender, and education level). In the empirical study, materialism and consumption attitude scales were applied to 149 teachers from Formosa, Goiás, Brazil. Results showed that gender influenced impulsiveness, with higher tendencies among women. Teachers in the final years of elementary school showed ambivalent behaviors, mixing impulsiveness and compulsiveness. There was also a negative correlation between age and materialism. The study highlights the importance of public policies focused on financial education and teacher appreciation, expanding the interdisciplinary debate between education, social psychology, and the sociology of consumption.
Materialism and consumption and purchasing attitudes among basic education teachers
Keywords: Materialismo; Atitudes de Consumo; Docentes da Educação Básica; Atitude de compra; Consumo - Compulsividade; Comportamento impulsivo - consumo; Materialism; Consumption Attitudes; Basic Education Teachers; Buying attitude; Consumption - Compulsiveness; Impulsive behavior - consumption; PSICOLOGIA::PSICOLOGIA SOCIAL; ECONOMIA DO BEM-ESTAR SOCIAL::ECONOMIA DO CONSUMIDOR; EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO